2015
DOI: 10.1093/gbe/evv133
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Family of Cysteine-Rich Peptides (MgCRP-I) fromMytilus galloprovincialis

Abstract: We report the identification of a novel gene family (named MgCRP-I) encoding short secreted cysteine-rich peptides in the Mediterranean mussel Mytilus galloprovincialis. These peptides display a highly conserved pre-pro region and a hypervariable mature peptide comprising six invariant cysteine residues arranged in three intramolecular disulfide bridges. Although their cysteine pattern is similar to cysteines-rich neurotoxic peptides of distantly related protostomes such as cone snails and arachnids, the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 104 publications
2
28
0
Order By: Relevance
“…These results suggest that considerable interindividual variability might occur in the inventory of myticalin genes across mussels, to the point that each individual could present a unique gene set, similarly to what has previously been reported for other AMPs in Mytilus spp. [ 5 , 39 ]. However, it remains to be established whether this variation is the result of extreme allelic variability linked to high heterozygosity [ 37 ], widespread genetic introgression within the M. edulis species complex [ 40 ] or whether it is linked to genome-wide phenomena of presence/absence variation, which have been previously described in oyster big defensins [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These results suggest that considerable interindividual variability might occur in the inventory of myticalin genes across mussels, to the point that each individual could present a unique gene set, similarly to what has previously been reported for other AMPs in Mytilus spp. [ 5 , 39 ]. However, it remains to be established whether this variation is the result of extreme allelic variability linked to high heterozygosity [ 37 ], widespread genetic introgression within the M. edulis species complex [ 40 ] or whether it is linked to genome-wide phenomena of presence/absence variation, which have been previously described in oyster big defensins [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of mussel transcriptome data suggested that, in contrast with most AMPs described so far in mussels [ 5 , 6 , 7 ], myticalins are preferentially expressed in the gills. Indeed, a number of myticalin transcripts could be de novo assembled to their full length using gill-derived RNA-seq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations